2012
DOI: 10.1002/ajp.22091
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Nucleotide Polymorphisms Reveal Patterns of Allele Sharing Across the Species Boundary Between Rhesus (Macaca mulatta) and Cynomolgus (M. fascicularis) Macaques

Abstract: Both phenotypic and genetic evidence for asymmetric hybridization between rhesus (Macaca mulatta) and cynomolgus (Macaca fascicularis) macaques has been observed in the region of Indochina where both species are sympatric. The large-scale sharing of MHC class II alleles between the two species in this region supports the hypothesis that genes, and especially genes involved in immune response, are being transferred across the species boundary. This differential introgression has important implications for the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
2
24
1
Order By: Relevance
“… showed that the rhesus and cynomolgus macaques from Indochina exhibited the greatest genetic diversity based on STRs and SNPs, respectively, perhaps reflecting the natural zone of interspecies hybridization in Indochina. This is consistent with an introgression of rhesus alleles that is both unique to cynomolgus macaques in Indochina and extends much broader than suggested by the current zone of hybridization described by Tosi et al. .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… showed that the rhesus and cynomolgus macaques from Indochina exhibited the greatest genetic diversity based on STRs and SNPs, respectively, perhaps reflecting the natural zone of interspecies hybridization in Indochina. This is consistent with an introgression of rhesus alleles that is both unique to cynomolgus macaques in Indochina and extends much broader than suggested by the current zone of hybridization described by Tosi et al. .…”
Section: Discussionsupporting
confidence: 89%
“…Genetic evidence of natural interspecies admixture between cynomolgus and rhesus macaques in Indochina, leading to gene flow well beyond the hybrid zone, is well‐documented . Thus, the majority of cynomolgus macaques employed in biomedical research in the United States also exhibit variable but unknown levels of admixture with rhesus macaques .…”
Section: Introductionmentioning
confidence: 99%
“…The 48 SNPs we selected for estimating proportion of rhesus macaque ancestry in cynomolgus macaques assigned at least some rhesus ancestry to all 391 cynomolgus macaque samples studied. The proportion of rhesus ancestry exceeded 45% in only three of these animals and averaged only 17%, less than had been previously reported for Indochinese cynomolgus macaques . This suggests that few, if any, of the 391 animals are first generation hybrids and that cynomolgus macaques in Indochina have been backcrossing to rhesus macaques or hybrids for many generations.…”
Section: Discussioncontrasting
confidence: 54%
“…Geographic contiguity has minimized genetic differences among cynomolgus macaques on the mainland of Southeast Asia, including Indochina, while extended isolation and founder effect associated with dispersal followed by renewed isolation have fostered genetic divergence of both Philippine and Mauritian cynomolgus macaques from other insular populations. Exacerbating this genetic difference between mainland and insular populations, cynomolgus macaques from Indochina experienced extensive introgression from rhesus macaques through hybridization after rhesus macaques diverged from the common ancestor shared between the two species, and exhibit a wide range of rhesus ancestry with an average value reported to approximate 30% . This broad range of variability in rhesus ancestry augments the genetic diversity among mainland cynomolgus macaques and increases their genetic difference from insular cynomolgus macaques.…”
Section: Introductionmentioning
confidence: 99%
“…The area of 15–20° N, covering central Myanmar, North, and Northeast Thailand, south of central Lao People's Democratic Republic (hereafter Laos) and central Vietnam was postulated as the hybrid zone between the two species (Fooden, ; Hamada et al, ; Malaivijitnond et al, ). Hybrids have also been claimed to occur south of this postulated hybrid zone towards the north of the Isthmus of Kra in the eastern half of the Indochina Peninsula (Tosi et al, ; Kanthaswamy et al, ; Osada et al, ; Satkoski Trask et al, ). Unidirectional gene flow from male‐rhesus macaque introgression into long‐tailed macaque populations has been proposed (Tosi et al, ; Kanthaswamy et al, ; Bonhomme et al, ; Stevison and Kohn, ; Yan et al, ).…”
mentioning
confidence: 98%